Business Payment Innovation on Customers - Alviana, S; Kurniawan, B; Millah, F S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to analyze and test the influence of E-Payment innovations in a place to eat or in department stores against customer response. The method used was a descriptive method of implementation covering data, analysis and also conduct surveys in the form of a questionnaire for customers. In this E-Payment research, there are several types of payment systems that are commonly used by users: digital wallets, online credit card, and digital money, in most cases, this E-Payment is a lot in use by users in Indonesia, because it is easy to use and also has features that make the user feel comfortable using E-Payment. The results gained with the advancement of E-Payment innovations are the number of E-Payment users in Indonesia who replace the payment system is cash. From 2018 until now E-Payment called Go-pay from Go-Jek is very much used by users in Indonesia, up to a number of 70.63% of users recognize more understanding of digital payment system services as well as digital finance and will be further increased. The conclusion of this research is the digital payment system or E-Payment will continue to innovate and develop so that users, especially in Indonesia, can feel the convenience of every transaction using e-payment either purchase goods or services.